2018
DOI: 10.1111/dom.13495
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of MYL‐1501D versus insulin glargine in patients with type 2 diabetes after 24 weeks: Results of the phase III INSTRIDE 2 study

Abstract: Demonstration of non-inferiority between MYL-1501D and reference insulin glargine for reduction of HbA1c during 24 weeks of treatment was achieved. The two treatment groups were similar in terms of secondary endpoints, including hypoglycaemia and nocturnal hypoglycaemia, local and systemic reactions, other safety variables, and immunogenicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(58 citation statements)
references
References 15 publications
(22 reference statements)
6
47
1
1
Order By: Relevance
“…Changes from baseline in terms of the incidence of TEAR were similar between the treatment‐switching and reference insulin glargine treatment sequences. These results suggest that both insulin glargine preparations demonstrated similar immunogenic potential, and switching patients from MYL‐1501D to reference insulin glargine and back to MYL‐1501D did not impact immunogenicity; these results further confirm the similar safety profiles of MYL‐1501D and reference insulin glargine demonstrated in earlier studies . The TEAR findings of the present study were similar to the immunogenicity and safety results of a study comparing another insulin glargine biosimilar (LY2963016) and reference insulin glargine in which the proportion of participants with detectable TEAR was similar between treatment groups, providing additional evidence to support the development and use of biosimilars or FOBs for therapeutics such as insulin …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Changes from baseline in terms of the incidence of TEAR were similar between the treatment‐switching and reference insulin glargine treatment sequences. These results suggest that both insulin glargine preparations demonstrated similar immunogenic potential, and switching patients from MYL‐1501D to reference insulin glargine and back to MYL‐1501D did not impact immunogenicity; these results further confirm the similar safety profiles of MYL‐1501D and reference insulin glargine demonstrated in earlier studies . The TEAR findings of the present study were similar to the immunogenicity and safety results of a study comparing another insulin glargine biosimilar (LY2963016) and reference insulin glargine in which the proportion of participants with detectable TEAR was similar between treatment groups, providing additional evidence to support the development and use of biosimilars or FOBs for therapeutics such as insulin …”
Section: Discussionsupporting
confidence: 89%
“…Although there were numerically more nocturnal hypoglycaemic events in the MYL‐1501D treatment sequence compared with the reference insulin glargine treatment sequence, this trend was probably not related to treatment because the trend was consistent across all three treatment periods, including when participants were receiving reference insulin glargine. Overall, the safety results support the safety results of INSTRIDE 1 and INSTRIDE 2 and indicate that the two sequence groups in the present study had equivalent safety profiles throughout the study at the end of the treatment period, and switching treatments had no impact on TEAEs, hypoglycaemic events, immunogenicity profiles, or other safety variables.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…MYL‐1501D has an amino acid sequence identical to that of reference insulin glargine, and comparative PK/PD studies demonstrated the bioequivalence of MYL‐1501D to both US and European insulin glargine in patients with T1DM . Similar results were observed in patients with T2DM; MYL‐1501D was shown to be non‐inferior to reference insulin glargine . The present data, in combination with the totality of the evidence, support the biosimilarity of MYL‐1501D to reference insulin glargine.…”
Section: Discussionsupporting
confidence: 86%
“…Overall, all three study drugs were well tolerated, and no significant safety issues arose. Results from this study provide further support that the proposed IG biosimilar MYL‐1501D may be appropriate for clinical use in patients with T1DM, as indicated by phase 3 studies …”
Section: Discussionsupporting
confidence: 65%